Prioritising Business Processes Design and Evaluation of the Prioritisation and Categorisation Method (PCM) - Ohlsson, Jens (SpringerBriefs in Business Process Management,, 2018)
This book addresses business process prioritisation - a problem in Business Process Management research that is often ill-structured and complex. The book introduces and describes the Prioritisation and Categorisation Method (PCM), a novel approach well aligned with today's business needs and climate. It embraces an explorative approach to facilitating process innovation and designing new processes in dynamic environments. Three classic theories are employed as the basis for PCM and summarised here - Ackhoff's interactive planning, Winograd and Flores' network of commitments, and Simon's bounded rationality. In addition, the book features a tutorial on a web-based tool that facilitates the application of PCM, together with two industry case studies that illustrate the method in practice and demonstrate its value.